Evaluation of Academic Information System Using Delone and Mclane Success Model: A Case Study ff Academic Information System Hasanuddin University - Andrisasmita Rachmat; Baharuddin Hamzah; Muhammad Niswar (Faculty of Computer Science Universitas Indonesia, 2022)
This study examines the effectiveness of the utilization (individual impact) of academic information systems at Hasanuddin University using the DeLone and McLean information system success model. This model has seven hypotheses to examine the construct relationships including system quality predicts user satisfaction (H1), information quality predicts user satisfaction (H2), system quality predicts actual use (H3), information quality predicts actual use (H4), user satisfaction predicts actual use (H5a), actual use predicts user satisfaction (H5b), user satisfaction predicts individual impact (H6), and actual use predicts individual impact (H7). We use structural equation modeling with Partial Least Square technique. The results show that H1, H2, H6, H7 have a significant positive impact and the remaining hypothesis have no significant positive impact. In conclusion, indicators that influence the effectiveness of using the system are on the system quality variable and the quality of information with the greatest influence on the quality of information.